INFLUENCE OF CONSUMER CONFIDENCE, PRICE, AND THE QUALITY OF SERVICE TO THE PURCHASING INTEREST OF USERS OF THE CITY TRANSPORTATION SERVICE ROUTEEK 03 CIANJUR - Wanda Laksniyunita (Jurnal Ekonomi, 2022)
This study aims to determine how much influence consumer confidence, price, and service quality have on the interest of users of public transportation services on the 03 Cianjur route, either partially or simultaneously. This type of research uses a descriptive method using primary data as research material. A total of 385 respondents were involved in this study. To obtain data, the authors use a questionnaire that was developed based on the indicators of previous research. Before the data was analyzed, the data was first tested for validity and reliability. In analyzing the data using multiple linear regression, t-test, F test, and coefficient of determination test with the help of SPSS 21. The results of the simultaneous significant test (F test) show that consumer confidence, price, and service quality simultaneously have a positive and significant effect. Meanwhile, the results of the partial significant test (t-test) show that the variables of trust and price have a positive and significant effect, for the service quality variable does not have a partially significant effect on buying interest. The value of the coefficient of determination is 0.217. This means that the variation of changes in the buying interest variable (Y1) can be explained or influenced by changes in the trust variable (X1), price (X2), and service quality (X3) of 21.7%. The remaining 78.3% is explained or influenced by other variables not examined in this study.